Isolation and identification of the oral bacteria and their characterization for bacteriocin production in the oral cavity - Alghamdi, Saad (Saudi journal of biological sciences, 2022)
Oral cavity is a diverse ecosystem which harbors immense diversity of microorganisms like fungi, virus and bacteria. Some of these microorganisms are involved in causing multiple infections. Oral flora is continuously changing due to connection with the external environment and produce bacteriocin against each other to compete for nutrient in this mini ecosystem. Current study was aimed to explore and compare the bacterial fauna of both healthy and non-healthy dental samples, by isolation and identification with biochemical tests to characterize the bacteriocin production. During study 120 swabs were taken from both healthy and unhealthy subjects. Samples were collected from the dental clinics of Makkah City, in sterile eppendorfs containing 1 ml nutrient broth, and were incubated overnight using shaking incubator. Bacteria were isolated following identification through Gram staining, microscopy and biochemical test. Total 15 strains of bacteria were isolated during the study amongst which 8 strains were gram positive and 7 strains were gram negative. The most dominant species of the gram positive strains was Streptococcus pneumoniae (n = 26). On the other hand, Escherichia coli (n = 26) was the prominent specie amongst the gram negative strains. Overall, the dominated family was Enterobacteriaceae (19.36%) followed by Streptococcaceae with 13.83% abundance. One of the most cariogenic strain Klebsiella pneumoniae (n = 14) was also isolated. The bacterial strain diversity between these two type of ecosystem was approximately the same, with slight variation in Shannon (HS:2.627187, NHS:2.653594) and Simpson diversity (HS:0.923461, NHS: 0.92684) index. The current research revealed that bacteriocin production in the Enterobacter species was prominent against Escherichia coli and Klebsiella pneumoniae. Apart from this other strains like Klebsiella pneumoniae and Exiguobacterium spp were also able to produce bacteriocin against Enterobacter species and Bacillus cereus respectively.